2019
DOI: 10.1111/jog.13909
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of progesterone on threatened miscarriage: Difference in drug types

Abstract: Aim To investigate whether treatment with progesterone would decrease the incidence of miscarriage in women who faced threatened miscarriage. Methods Randomized controlled trials (RCT) were identified by searching PubMed, Embase, Cochrane Library and Web of Science. Trials were included if they compared progesterone with placebo, no treatment or any other treatment given in an effort to treat threatened miscarriage. Pregnant prophylaxis drugs were not included without strict progesterone type, language and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Based on data from recent systematic reviews and meta-analyses, oral dydrogesterone effectively prevents miscarriage in pregnant women experiencing threatened miscarriage 1618. The meta-analysis by Carp et al, which collated data from five randomized trials including 660 patients, reported that the miscarriage rate was 13% in women on dydrogesterone versus 24% in the control group (odds ratio [OR] 0.47, 95% confidence interval [CI] 0.31–0.7, 11% absolute reduction in miscarriage rate) 16.…”
Section: Review Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Based on data from recent systematic reviews and meta-analyses, oral dydrogesterone effectively prevents miscarriage in pregnant women experiencing threatened miscarriage 1618. The meta-analysis by Carp et al, which collated data from five randomized trials including 660 patients, reported that the miscarriage rate was 13% in women on dydrogesterone versus 24% in the control group (odds ratio [OR] 0.47, 95% confidence interval [CI] 0.31–0.7, 11% absolute reduction in miscarriage rate) 16.…”
Section: Review Summarymentioning
confidence: 99%
“…Similar findings were reported by Wahabi et al: oral progestogens (dydrogesterone and micronized progesterone) were found to reduce the rate of miscarriage compared with no treatment (risk ratio [RR] 0.57; 95% CI 0.38–0.85; three trials; 408 patients) 19. Wang et al pooled data from eight randomized controlled trials, including 845 women with threatened miscarriage, and reported that women receiving dydrogesterone were at a lower risk of miscarriage (RR 0.49, 95% CI 0.33–0.75) than women on natural progesterone (RR 0.69, 95% CI 0.40–1.19) 18. Furthermore, women treated with oral progestogens demonstrated a lower risk of miscarriage (RR 0.55, 95% CI 0.38–0.79) than those on vaginal progestogens (RR 0.58, 95% CI 0.28–1.21) 18…”
Section: Review Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In the 50–80s of the last century, the main indication for administration of progestins was pregnancy maintenance. Today, the gold standard is the use of dydrogesterone (Duphaston) and progesterone (Utrogestan), their efficacy has been proven by many clinical studies [ 26 30 ].…”
Section: Clinical Use Of Gestagensmentioning
confidence: 99%
“…15 A local survey done in ordinary areas of Karachi by Ayub M et al 16 highlighted that women treated with progesterone, had reduced rates of abortion. Wang XX et al 17 noted oral progesterone to lower the risk of miscarriage (RR 0.55, 95% CI: 0.28-1.21) in pooled data analyzing data from 8 RCTs comprising of 845 women. Researchers have also indicated that women having low levels of progesterone (less than 35 mmol/L) have 24 fold more chances (OR 23.8, 95% CI 6.5-86.6%, p value < 0.0001) of miscarriage in comparison to those pregnant women having high levels of progesterone (equal or above 35 mmol/L).…”
Section: Treatment Of Threatened Miscarriagementioning
confidence: 99%